A Comparison of Developmental and Maternal Toxicity of Perfluoro Octane Sulfonate (PFOS) In Mouse: Evaluation of Histopathological and Behavioral Changes: Comparison of toxicity of Perfluoro octane sulfonate (PFOS) in Mouse - Freshteh Mehri,; Mehrdad Faizi,; Farzad Kahrizi,; Baharak Mohammadzadeh Asl,; Jalal Pourahmad, (Iranian Journal of Pharmaceutical Sciences, 2016)
Perfluorooctanesulfonate (PFOS) is a widely spread environmental contaminant. It accumulates in the brain and has potential neurotoxin effects. Due to chemical properties, PFOS shows persistency in the environment and therefore has potential hazardous effect. The risk of possible intra uterine exposure to PFOS poses a health concern for developmental effects. The goal of this study was survey of histological and behavioral changes made by PFOS in pregnant mice and their fetuses using common behavioral assays and H&E staining. In the present study, doses of PFOS (1, 10, 20 mg/kg) were given orally to pregnant mouse from gestational day (GD) 0 to GD14; then on the day 15, Behavioral experiments including (open field and passive avoidance) were used to assess toxic behavioral changes such as memory impairment and anxiety. After behavioral evaluations, fetuses were dissected on day 15 of gestation and morphological and histological studies on pregnant mouse brain and her fetus were carried out using haematoxylin-eosin staining method. Our findings showed that PFOS could induce neurotoxicity in pregnant mouse especially by induction of abnormalities in dentate gyrus of hippocamps and disruption of neurobehavioral functions .Besides in her fetus; PFOS produced significant changes in brain, liver, and thyroid gland in comparison with untreated control mouse fetus. As a conclusion, PFOS can cause both neurobehavioral and developmental toxicity in pregnant mouse and her fetus.